An Analysis of the Influence of Financial Performance on Profit Growth Predictions (An Empirical Study of Manufacturing Companies in the Real Estate and Property Subsector) - Ira Yudi Farmawati; Yundi Permadi Hakim; Bowo Lestono (Green Publisher Indonesia, 2026)
This study aims to determine the influence of financial performance in predicting profit growth in manufacturing companies in the Real Estate and Property sub-sector on the Indonesia Stock Exchange for the 2017–2022 period. The sampling technique in this study used a purposive sampling method and obtained a sample of 37 companies. The analysis technique used is multiple linear regression analysis and Moderated Regression Analysis (MRA) using SPSS software version 25.0. The results of this study indicate that WCTA, DER, and NPM have no effect on profit growth, while TATO and firm size have an effect on profit growth, and simultaneously WCTA, DER, TATO, UP, and NPM have an effect on profit growth. ROA is able to moderate the relationship between WCTA, TATO, company size, and NPM on profit growth, while ROA is not able to moderate the relationship between DER and profit growth. It is hoped that this research can be used as a consideration for manufacturing companies in the Property and Real Estate sub-sector in order to improve their financial performance so that they will be able to attract more investors and pay attention to the factors that can affect profit growth.